Salmonella - still a threat? Epidemiological analysis of infecion - Kinga Ruszel; Robert Dubel; Wiktoria Chodun; Barbara Nieradko-Iwanicka (Kazimierz Wielki University, 2021)
Salmonella infection causes morbidity and mortality throughout the world with the host immune response varying depending on whether the infection is acute and limited, or systemic and chronic. Global Salmonella infection, especially in developing countries, is a health and economic burden. These pathogen are responsible for millions of cases of food-borne illness each year, with substantial costs measured in hospitalizations and lost productivity. The growing number of bacteria resistant to the antibiotics commonly used to treat infections with this bacterium increases the use of alternative treatments. The species Lactobacillus and Bifidobacterium are the most commonly used probiotics to treat infectious diseases, including antibiotic diarrhea and traveler's diarrhea. It is a Gram-negative, non-spore-forming, rod-shaped and facultative anaerobic bacterium. However, they have the ability to survive inside infected cells. These bacteria cause various clinical forms of disease. The most dangerous sticks of typhoid fever (Salmonella typhi) and paradurium (Salmonella paratyphi) multiply only in the human body and cause a very serious infectious disease - typhoid fever. In turn, non-malignant salmonella, Salmonella bongori and countless serological varieties of Salmonella enterica colonize the digestive tract of many animal species and are pathogenic to humans, causing gastroenteritis, i.e. acute salmonellosis, sometimes classified as food poisoning. All Salmonella infections begin with ingestion with contaminated food or water.